The Politics of Music: Women’s Music Education in the United States in the late 18th Century - Evans, Christa Pehl (Current Musicology, 2020)
This article provides a background for these varying streams of thought and examines their intersection at the debate about what type of music is suitable for women to learn. That women should learn music was not a point of contingency, but how they should learn, what type of music they should study, and what role music would play in their lives were subjects of discussion.